PENAMBAHAN TEPUNG BAWANG PUTIH (Allium sativum L) SEBAGAI FEED ADDITIF DALAM RANSUM TERHADAP PENAMPILAN AYAM PEDAGING - Siti Dharmawati; Nordiansyah Firahmi; Parwanto Parwanto (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2013)
This study is aimed to acknowledge garlic efficiency as feed additive on concentrate feed in broiler’s performance. This research was conducted at Farm and Agriculture Laboratory of Agriculture Faculty of Lambung Mangkurat University. The research was conducted from July till August 2012. The experiment used Complete Random Sampling Method by 5 treatments and was repeated 4 times which consisted of 4 broilers for each. The garlic meal was mixed into the diet according to the treatment : P0 (no garlic extract), P10(0,10% garlic extract), P15(0,15% garlic extract), P20(0,20% garlic extract), P25 (0,25% garlic extract). The observation involved feed intake, body weight increase, feed conversion and final body weight.The results showed that garlic supplementation into the feed significantly affected to feed conversion, but did not affect directly into feed intake, body weight increase and final body weight. And the most efficient feed conversion that garlic meal treatment of 0,10% (P10) – 0,25% (P25) showed as the best result; 1,51 – 1,54. Performance Index got significantly difference at treatment P15, P20 and P25 about 380,05—383,83.